The Private Sector in Iraq: Reality and Constraints - Abdul-Hussain, Ali Jabber; Abdul-HadiUbaid, Huda (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to study the reality of the private sector in Iraq, determine the most important obstacles and difficulties encountered, as discussed in this research the private sector in Iraq, by explaining the reality of the private sector at different periods of time, from the beginning of establishment in 1921 until nationalization in 2003, the reality of the private sector was addressed during the first three periods, reflected the reality of the private sector in the monarchy. The second is about the private sector during the Republican era, the events that this time period witnessed reflect the fragility of the role that the Iraqi private sector lives under the control of the state. The third era determine the reality of the private sector in light of the wars and sanctions imposed, the most important obstacles facing the private sector were discussed, displacement from exercising the real role in the development of the economy, by using the state's financial policy tools represented by public expenditures and public revenues. The study found that many investments were reluctant to invest at home, as a result of the deteriorating security conditions, and the absence of laws and legislation necessary to establish large projects, the state’s dependence on oil, the neglect of other sectors and their lack of diversification weakened the private sector, in particular, the state adopted an open-door policy after 2003 in importing goods from abroad, local products were discouraged, it was the reason for the displacement and killing of the private sector in contributing to the Gross domestic product.